SUSTAINABILITY REPORTING: MEKANISME TRANSFORMASI ATAU SARANA GREENWASHING - Rosalinda, Zhafirrah; Mukhtaruddin (Musytari : Jurnal Manajemen, Akuntansi, dan Ekonomi, 2025)
The increasing global emphasis on sustainability has prompted companies to adopt sustainability reporting as a tool for transparency and accountability. Ideally, sustainability reporting serves as a transformation mechanism that enhances corporate strategies by integrating environmental, social, and governance (ESG) considerations. Prior research suggests that sustainability reporting can improve firm value by increasing transparency, operational efficiency, and investor attractiveness. However, in practice, some companies exploit sustainability reporting as a greenwashing strategy, using it as a marketing tool to enhance their corporate image without genuine sustainability efforts. The lack of stringent reporting standards allows firms to make misleading claims, which can erode stakeholder trust and undermine the credibility of sustainability reporting. This study employs a systematic review method to examine whether sustainability reporting genuinely drives corporate transformation or merely serves as a facade for greenwashing. The findings highlight the dual role of sustainability reporting—while it has the potential to enhance firm value through transparency and ESG integration, its misuse as a greenwashing tool remains a significant concern. Strengthening reporting standards and aligning sustainability initiatives with business strategies are essential to ensuring the authenticity and effectiveness of sustainability reporting.